Identifikasi Karakteristik Neo Vernakular Pada Fasad Bangunan Kantor DPRD Sumut - Fransiskus Sanderwin Gea; Dara Wisdianti (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
. The effort to re-visualize regional architectural elements combined with modern touches is known as neo-vernakular architecture. In North Sumatra, there are various ethnic groups, including Batak, Mandailing, Malay, and others, each possessing rich traditional architectural values. This study aims to identify and analyze traditional architectural elements applied to the façade of the North Sumatra Regional House of Representatives (DPRD) building. The DPRD North Sumatra building is one of the government buildings that functions as a workplace for representatives of the people, council members, and the secretariat in carrying out governmental duties and public services. The building is located on Jalan Imam Bonjol with an area of approximately 8,000 square meters. This study uses a qualitative descriptive method with data collection techniques through direct field surveys and literature studies related to the façade design of the DPRD North Sumatra building. The results show that the neo-vernakular character on the building façade is represented through several architectural elements, such as exposed columns, sunshading, opening forms, and other supporting elements that reflect a combination of traditional and modern architectural features.